Effect of Performance and Exhaust Emission using Liquid Phase LPG Sequential Injection as an Alternative Fuel in Spark Ignition Engine - Tukiman, Mohd Mustaqim; Osman, Shahrul Azmir; Fawzi, Mas; Mustaffa, Norrizal; Madon, Rais Hanizam (International Journal of Integrated Engineering, 2018)
LPG has a higher research octane number (RON) and low carbon to hydrogen ratio contains. Thus LPG has prospects to gain more performance and reducing the exhaust emission in spark ignition (SI) engine. The objectives of this study are to identify the influence liquid phase LPG system tested on SI engine and investigate the performance and exhaust emission of LPG and gasoline. The contain LPG has 60% butane and 40% propane, according to Materials Safety Data Sheet (MSDS). The experiment was operating on a 1.6 Liter, 4 inline cylinders from a Proton Gen 2 (S4PH). The engine fuel delivery was equipped with Multiport Injection (MPI) system. Injectors LPG Liquid Sequential Injection (LSI) was mounted at close intake valve without disturbing gasoline injectors. To control the LPG injector system, the piggy-back system was installed as to emulate the stock Electronic Control Unit (ECU). The engine was tested via chassis dynamometer at steady state conditions to analyze the Brake Power (BP) and Brake Torque (BT) at a desired engine speed from 1500rpm to 4000rpm with increments of 500rpm. Meanwhile, the Throttle Position (TP) was varied at four conditions that were 25%, 50%, 75% and 100% for every single engine speed. The result of the performance showed liquid phase LPG increased BT and BP in the range of 3% to 7%, BSFC was reduced in the range 21% to 52%. The exhaust emission from carbon monoxide (CO) was decreased in the range of 2% to 19%, exhaust emission from a hydrocarbon (HC) was emitted increment in the range of 40% to70% and nitrogen oxide (NOX) exhaust emission was elevated in an average of 60% in comparison with gasoline. The LPG LSI system is more effective than gasoline in Spark Ignition (SI) engine at lower engine speed (1500rpm to 2500rpm) due to low Brake Specific Fuel Consumption (BSFC) and exhaust emission.